Digital Islamic Education: The Role of Islamic Information in Virtual Spaces in Shaping Character - Devi Fatwanti; Nur Ainiyah; Ida Nursida; Fitria Wahud; Mar’atun Sholiha; Muh Irfan Ali (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Digital transformation has significantly changed the way people access Islamic information through various digital platforms. While this development has expanded access to Islamic learning resources, it has also introduced challenges related to the spread of unreliable information, highlighting the need to strengthen Islamic digital literacy. This community service program aimed to enhance participants' Islamic digital literacy, optimize the use of digital Islamic education platforms, and reinforce Islamic character in the responsible use of virtual spaces. The program employed an educational-participatory approach consisting of preparation, educational sessions, interactive discussions, hands-on practice with digital platforms, mentoring, and evaluation through observations, pre-test and post-test questionnaires, and reflective discussions. The collected data were analyzed using descriptive qualitative methods. The results demonstrated significant improvements in participants' ability to identify credible sources of Islamic information, apply the principle of tabayyun (information verification), and utilize digital Islamic education platforms more effectively. Furthermore, participants exhibited more selective, critical, and responsible attitudes toward receiving and disseminating religious information in digital environments. The program also strengthened the internalization of Islamic character values, including honesty, trustworthiness, responsibility, proper conduct (adab), and digital media ethics. These findings suggest that digital Islamic education plays a strategic role in enhancing digital literacy while fostering adaptive character development without compromising Islamic values.